Pengaruh Kepuasan Kerja, Motivasi Kerja dan Remunerasi terhadap Turnover Karyawan pada Subsektor Perhotelan - Intan Maesti Gani; Kamsariaty Kamsariaty; Lily Yuntina; Rintis Eko Widodo; Agus Suhendra (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to analyze the influence of job satisfaction, work motivation, and remuneration on employee turnover in the hospitality subsector, both partially and simultaneously. The method used is a descriptive qualitative approach with a systematic literature review (SLR), where secondary data is obtained from reputable national and international journal articles that have gone through a peer review process, selected through the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) protocol. Data analysis was conducted using content analysis and thematic analysis. The results of the study indicate that: 1) Job satisfaction has a negative effect on employee turnover in the hospitality subsector; 2) Work motivation has an effect on employee turnover in the hospitality subsector; 3) Remuneration has an effect on employee turnover in the hospitality subsector. The managerial implications of this study indicate that hotel management needs to simultaneously strengthen job satisfaction, work motivation, and remuneration as an integrated strategy to reduce turnover rates and build long-term human resource stability.